Volumetric and viscometric studies of copper soap urea complex derived from various vegetable oils in methanol benzene mixture. (Bulletin of Pure and Applied Sciences-Chemistry, 2019)
The density and viscosity of Cu (II) soap urea  complex derived from four edible oils (mustard,  groundnut, sesame, soyabean) in non-aqueous  solvents of varying composition has been  determined at constant temperature. The results  were used to determine the critical micelle  concentration (CMC), soap-solvent interactions  and the effect of chain length of the soap urea  complex molecule on various parameters. The  CMC values in higher volume % of methanol are  higher those in higher volume % of benzene, with  regards to chain length of the soap urea complex  CMC value follow the order: CSoU>CSeU> CGU > CMU The conclusions with regard to soap- urea  complex and soap- solvent interaction have been  discussed in terms of well-known Masson’s and  Jones- Dole equations. This vital information  plays an important role in various industrial and  biological applications.
Keywords: Cu(II) soap urea complex; edible oils; soap- solvent interaction; CMC; density and viscosity